Studies on Antibacterial Activity of Asterella angusta (Steph.) Kachroo. against some Pathogenic Bacteria - Khanam, Rubina Khanam*, B.L.Chaudhary, Shabana (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The In vitro antibacterial activity of whole thallus of Asteralla angusta andÃ‚Â  its fractions petroleum ether, benzene, acetone, methanol, ethanol, and aqueous extracts were tested against the growth of four human pathogenic gram negative bacteria namely Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumonie and two gram positive bacteria Bacillus subtilis and Staphylococcus aureus using agar well diffusion technique. The plant showed significant antibacterial activity against all the organisms. The maximum antibacterial activity was observed in ethanolic extract against Pseudomonas aeruginosa and minimum activity was observed in petroleum ether extract against Proteus mirabilis. The phytochemical analysis of the extract indicated the presence of saponin, flavonoids, and carbohydrates. The inhibitory effect of the extract was compared with standard antibiotics, streptomycin.